The Effect of Lavender Aromatherapy on Anxiety of Primigravid Pregnant Women in Tobongon Village - Firda Ponelo; Rifzul Maulina; Widia Shofa Ilmiah (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Anxiety during pregnancy is an issue that is increasingly receiving attention in the field of maternal health. Anxiety can harm fetal development and maternal mental health. High anxiety can lead to complications such as premature labor and low birth weight. Aromatherapy, especially the use of lavender essential oil, has been shown to have a calming effect that can help relieve anxiety. Previous studies have shown that lavender can reduce levels of stress hormones, such as cortisol, which contribute to feelings of anxiety. to measure the effect of lavender aromatherapy on anxiety levels in primigravida pregnant women. The research method used in this study was a pre-experiment with a pre-post group test. The study sample consisted of 20 primigravida pregnant women. Measurement of anxiety levels was carried out using the HARS Anxiety Scale measuring instrument before and after treatment. Lavender aromatherapy was given for 30 minutes every day for two weeks. The data obtained were analyzed using a paired t-test. Results: differences in anxiety levels of pregnant women in the third trimester between before and after being given lavender aromatherapy, this is evidenced by the mean value of the pre-test results of 25.5 but the mean value of the post-test results of 23.2. This is reinforced by the results of the t-test obtained to count 7.254. Furthermore, based on the results of the calculation of the level of significance, it shows that the value of